Clinical manifestations of familial hypercholesterolemia: a case series - Shankar Rao, Subramani K.; Chikkabasavaiah, Nagamani A.; Hathi, Varshit D.; Jadhav, Santosh; Noorain, Saleha; Gowda, Ravinandan; Nanjappa, Manjunath C. (International Journal of Advances in Medicine, 2021)
Familial hypercholesterolemia is a rare, monogenic, co-dominant, life-threatening disorder resulting from loss of function mutations in the genes responsible for synthesis of low-density lipoprotein receptors or apo-B genes or gain of function mutations in PCSK9 genes in the liver which affects 0.2% of the population. It is characterized by severe lifelong elevation of LDL cholesterol and by development of xanthelasma, xanthomas, premature coronary artery disease and peripheral artery occlusive disease. Most patients develop PCAD and aortic stenosis before the age of 20 years and die before 30 years of age. The diagnosis of FH is usually based on clinical presentation and commonly used criteria are the Dutch lipid clinic network criteria, Simon Broome criteria or the WHO criteria. We encountered four cases of familial hypercholesterolemia over last 10 years. All the four patients presented with effort angina and all were found to have obstructive coronary artery disease oncoronary angiogram and two of them had severe supravalvular aortic stenosis. All four patients were on dietary modifications, high intensity statin and cholesterol absorption inhibitor. Two patients underwent coronary artery bypass grafting with aortoplasty, one patient underwent coronary artery bypass grafting and one patient underwent percutaneous transluminal coronary angioplasty. Familial hypercholesterolemia leads to development of life-threatening manifestations early in the second and third decades of life. Early diagnosis, aggressive treatment and control of risk factors and cascade screening are important in management and will help to reduce the morbidity and mortality associated with this disease.